Analysis of ridges and grooves shape in grating coupler for optimization of integrated optics sensor structures. - Struk, Przemysław (Photonics Letters of Poland, 2022)
The paper presents a theoretical analysis of a sensor structure based on a planar waveguide and grating coupler designed to determine selected physical properties of blood – hemoglobin concentration and oxidation level. In particular analysis were focused on optimization of selected geometrical properties of grating coupler (shape of ridges and grooves) to obtain maximum efficiency of uncoupling of light from the sensor structure. The analysis were carried out for three type of ridges and grooves shape in grating coupler: rectangular, triangular and sinusoidal. Full Text: PDF References I. . Singh, A.Weston, A. Kundur, G. Dobie, Haematology Case Studies with Blood Cell Morphology and Pathophysiology; Elsevier: Amsterdam, The Netherlands, (2017). DirectLink P. Jarolim, M. Lahav, SC. Liu, J. Palek, "Effect of hemoglobin oxidation products on the stability of red cell membrane skeletons and the associations of skeletal proteins: correlation with a release of hemin", Blood 76, 10 (1990). CrossRef E. Beutler, J. Waalen, "The definition of anemia: what is the lower limit of normal of the blood hemoglobin concentration?", Blood 107, 5 (2006). CrossRef M. Kiroriwal, P. Singal M. Sharma, A. Singal, "Hemoglobin sensor based on external gold-coated photonic crystal fiber", Optics & Laser Technology 149, 107817 (2022). CrossRef A. A. Boiarski, J. R. Busch, B. S. Bhullar, R. W. Ridgway, V. E. Wood, "Integrated optic sensor with macro-flow cell", Proc. SPIE Integrated Optics and Microstructures 1793 (1993). CrossRef L. Cheng, S. Mao, Z. Li, Y. Han and H. Y. Fu, "Grating Couplers on Silicon Photonics: Design Principles, Emerging Trends and Practical Issues", Micromachines 11, 666 (2020). CrossRef P. Struk, "Design of an Integrated Optics Sensor Structure Based on Diamond Waveguide for Hemoglobin Property Detection", Materials 12, 175 (2019). CrossRef P. Struk, "Numerical analysis of integrated photonics structures for hemoglobin sensor application", Phot. Lett. Poland 12, 2 (2020). CrossRef P.V. Lambeck, "Integrated optical sensors for the chemical domain", Meas. Sci. Technol. 17, (2006). CrossRef W. Lukosz, "Integrated optical chemical and direct biochemical sensors", Sens. Actuators B Chem 29 (1995). CrossRef P. Struk, T. Pustelny, K. Gołaszewska,E. Kaminska, M.A. Borysiewicz, M. Ekielski, A. Piotrowska, "Hybrid photonics structures with grating and prism couplers based on ZnO waveguides", Opto-Electron. Rev. 21, (2013). CrossRef P. Struk, "Design of an integrated optics sensor structure for hemoglobin property detection", Proc. SPIE 11204, (2019). CrossRef OptiFDTD Technical Background and Tutorials - Finite Difference Time Domain Photonics Simulation Software, Optiwave Systems Inc. (2008). DirectLink K. Yee, "Cutoff Frequencies of Eccentric Waveguides", IEEE Transactions 14, 3 (1966). CrossRef